1997
DOI: 10.1007/s11663-997-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multineedle electroresistivity probe for measuring bubble characteristics in molten metal baths

Abstract: Precise information on the behavior of rising bubbles in molten metals is of essential importance for the enhancement of current metal-refining processes as well as the development of new refining processes agitated by gas injection. In particular, the total interfacial area between bubbles and molten metal is a key parameter, but it cannot be evaluated unless the shape of bubbles is given. Getting information on the shape of rising bubbles has been very difficult for nontransparent liquids. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Previous experiments using electroresistivity probe [18,19] have shown that the shape of a bubble can be correlated as a function of the modified Weber number, We, and the modified Reynolds number, Re, as shown in Fig. 9.9.…”
Section: Single Bubble In Still Liquidmentioning
confidence: 89%
“…Previous experiments using electroresistivity probe [18,19] have shown that the shape of a bubble can be correlated as a function of the modified Weber number, We, and the modified Reynolds number, Re, as shown in Fig. 9.9.…”
Section: Single Bubble In Still Liquidmentioning
confidence: 89%
“…[12,20] Figure 11 shows the relative occurrence in frequency of the four turbulent motions in the He-Wood's metal bubbling jet together with those in an air-water bubbling jet. [17] In the region near the centerline (r ϭ 0), the relative occurrence in frequency of each turbulent motion was approximately 0.25, and, hence, there was no coherent structure there. In a radial region of 0 Ͻ r/b u Շ 1.0, the relative occurrence in frequency of sweep became the high- est, that of ejection followed it, and the relative occurrence in frequency of inward interaction was the lowest.…”
Section: -Quadrant Classification Methodsmentioning
confidence: 98%
“…[17] The bubbles had a cross section as illustrated in Figure 5 and were classified as skirted bubbles. These bubbles rose almost straight upward and, hence, brought about the radial distribution of gas holdup with the aforementioned profile.…”
Section: Bubble and Mean Wood's Metal Flow Characteristicsmentioning
confidence: 99%
“…A selection of intrusive and nonintrusive bubble measurement techniques with relevant references are summarized in Table I. The bubble traveling in liquid can be detected by simple optical observations, optical [9] and electrical [10][11][12] probe measurements, advanced ultrasound Doppler velocimetry (UDV) [14][15][16] X-ray imaging [17] neutron radiography, [26] and sophisticated resonant spectroscopy [21][22][23][24][25] allowing measurements of the bubble size distribution in the pool.…”
Section: Introductionmentioning
confidence: 99%
“…[33] The steam bubbles transport in the primary system of an HLM cooled reactor, and the possibility that bubbles can reach the core is highly sensitive to the terminal rise velocity for submillimeter bubbles. [34] Unfortunately, there are no data available Electromagnetic sensing Optical probe [9] Capacitive or inductive measurements Conductivity probes [10][11][12] Conductivity of the liquid channel Hot wire anemometer [13] Acoustical methods:…”
Section: Introductionmentioning
confidence: 99%